Improving milk antioxidant activity and nutritional composition through the incorporation of Argania spinosa (L.) by-products in goat’s diet - Mercha I.; Lakram N.; Kabbour M.R.; Bouksaim M.; Zkhiri F.; El Maadoudi E.H. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Many studies reported that beneficial bio molecules compounds have been identified from various parts of the Argania spinosa (L.) Skeels and can play an important role in fighting diseases. Certainly, Morocco includes the most important rate of production, but the different by-products of this tree are not valorised. In this present study, we investigate the effect of the incorporation of the Argane tree’s by-product in goat’s diet, on the antioxidant activity, the microbiological quality, the physicochemical and mineral composition of Alpine goat milk collected from Essaouira, Morocco. The preliminary results of this study revealed a remarkable improvement in several of the analysed parameters, especially the fat content with an increase of 51.21%, which remains the most noteworthy. Microbiological analysis showed that the mean mesophilic aerobic flora count for goats consuming the Argane by-product diet (AD) was 1.38.107±2.67.107 Cfu.mL-1 comparing to 2.96.107 ± 5.42.107 Cfu.mL-1 for those consuming the Control Diet (CD). The total phenolic content of milk collected from goats consuming AD varied from 17.29 ± 0.61 to 22.65 ± 1.15 mg GAE/g of DM, while that the total phenolic content of milk collected from goats consuming CD varied from 10.74 ± 0.39 to 12.46 ± 0.33 mg GAE/g of DM. Furthermore, mineral analysis demonstrated that AD milk samples are rich in potassium, magnesium and other minerals with many health benefits.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)